Dataset of knowledge retention and learning satisfaction in patient-nurses safety - Rose A. Naina; Deena Clare Thomas; Johari Daud Makajil; Rista Fauziningtyas (Elsevier Inc., 2025)
This dataset contains information on knowledge retention and learning satisfaction in the context of patient–nurse safety education. The data was collected through structured questionnaires administered to participants before and after implementing a safety-focused learning module. The dataset includes demographic variables, pre- and post-assessment scores measuring knowledge retention, and feedback on participants' satisfaction with the learning experience. Data were compiled to facilitate the identification of patterns, relationships, and associations between knowledge acquisition and satisfaction with educational interventions. The dataset is presented in a tabular format to enable further analysis and application in educational program evaluations or other related fields. The reuse potential includes informing curriculum development, identifying effective teaching strategies, and benchmarking learning outcomes.